Effects of Non-intubated Video-Assisted Thoracic Surgery on Patients With Pulmonary Dysfunction - Deng, Shiyu; Cen, Yanyi; Jiang, Long; Lan, Lan (Frontiers in Surgery, 2022)
Background: Non-intubated video-assisted thoracoscopy (NIVATS) can be safely performed in lung volume reduction surgery for patients with severe pulmonary dysfunction. However, there is still no cohort observation on the effects of NIVATS on patients with pulmonary dysfunction undergoing different types of thoracic procedures. This retrospective study aimed to observe the effects of NIVATS for this kind of patient. Methods:328 patients with moderate to severe obstructive pulmonary dysfunction, who underwent VATS, were retrospectively collected from June 1st, 2017 to September 30th, 2019. Patients in NIVATS were case-matched with those in intubated VATS (IVATS) by a propensity score-matched analysis. The primary outcome was the comparison of perioperative values, the secondary outcome was the risk factors for postoperative clinical complications which were identified by binary logistic regression analysis. Result: There were no differences in demographics and preoperative values of pulmonary function between NIVATS and IVATS groups after being matched. The duration of surgery and anesthesia had no difference (P=0.091 and P=0.461). As for the postoperative recovery, except for the mean intensive care unit (ICU) stay was longer in the IVATS group than in the NIVATS group (P=0.015), the chest tube removal time and the postoperative hospital stay had no difference (P=0.394 and P=0.453), and the incidence of postoperative clinical complications also had no difference (P=0.121). The binary logistic regression analysis revealed that the history of pulmonary diseases, anesthesia method, and surgical location were risk factors of postoperative clinical complications. Conclusion: For patients with pulmonary dysfunction when undergoing different types of thoracic procedures, the NIVATS can be performed as effectively and safely as the IVATS, and can reduce the ICU stay.